Skills To Guide Discussions and Small Groups and Individuals - Amini, Amini; Pane, Alya Rina Armalia; Utami, Azizi Anggi; Antika, Sindi; Aulia, Tazkya (EDUCTUM: Journal Research, 2023)
This research aims to explain the skills of guiding discussions in small groups and individuals. using descriptive methods in qualitative research. The descriptive method in research is research for the purpose of explaining or describing events, objects, circumstances, or variables which are explained using numbers and words. The type of descriptive method in qualitative research is a type of library research from document literature from various sources related to the skills of guiding discussions and small groups and individuals. The skill of guiding small group discussions carried out by teachers is a teacher trainee skill. In teaching activities there are times when conducting group discussion activities. Discussion activities involve mental and emotional activities that can improve interpersonal relationships. So the teacher's skills in guiding small group discussions are needed to ensure the continuation of the discussion effectively. In this learning, the learning atmosphere is developed for... critical thinking and problem solving skills, collaboration and communication, creativity and innovation.